The Effect Of Health Education Using Direct Demonstration Method On Compliance In The Use Of Personal Protective Equipment (PPE) In Sugar Cane Farmers Group In Desa Banyuputih Kidul , Kecamatan Jatiroto, Kabupaten Lumajang - Huda, Nuril; Abidin, Zainal; Roisah, Roisah (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2024)
Personal protective equipment is very important in carrying out work which can cause work accidents, so health education using direct demonstrations makes a huge contribution to change respondent behavior. So with direct demonstrations it was hoped that people would understand and remember more quickly. The aim of this research wss to identify the effect of direct demonstration method health education on compliance with the use of personal protective equipment (PPE) in sugar cane farmer groups. The research method used in this research was a pre-experimental one group pre test and post test design. The population of this study was a group of sugar cane farmers in Desa Banyuputih Kidul , Jatiroto subdistrict, Lumajang district with a sample of 30 respondents. The sampling technique used Amount sampling with a data collection sheet, observation sheet and analyzed using the SPSS statistical test, the Willcoxon test showed that the results were p value = a = 0.000, a <0.05. The results of the research before health education using the direct demonstration method showed that most of the compliance was not good, 30 people (100%) and after health education using the direct demonstration method, the majority of compliance was good, 17 people (56.7%), and there was an influence of health education using the method. direct demonstration of the level of compliance among sugar cane farmer groups. It is hoped that this research can increase more efforts and support from village officials and farmer group administrators in providing personal protective equipment (PPE), and health education using the direct demonstration method can be applied in educational services in village communities, especially in farmer groups with other implementations.